"Me hace dudar de tu venida": mobile immigrants, colonial enterprise, familial obligation, and the complications of a transatlantic marriage. Issue 3 (2nd September 2022) - Cromwell, Jesse
ABSTRACT: Bourbon reformers encouraged impoverished Canary Islanders to repopulate and cultivate peripheral locales of the empire throughout the eighteenth century. However, this mobility clashed with the family obligations of those settlers. In 1759, at the age of eighteen, Domingo Galdona left Tenerife in the Canary Islands to make his fortune in Venezuela, settling in Cumaná and accumulating a handsome cacao plantation by his hard work. This rags-to-riches story was complicated thirteen years later when Galdona's wife, Antonia Guerra y Baute, filed a suit with colonial administrators demanding that he return to married life with her and their daughter in Tenerife or, alternatively, take them to live with him in Cumaná. Guerra y Baute's suit accused Galdona of bigamy, smuggling, domestic abuse, faking his own death, and abandonment. Domingo and Antonia's case was also a story about immigration and the state. His troubles with the legal apparatus of empire demonstrated how migration complicated bedrock principles of domestic society in the Iberian world. The frustrating ambiguities of Domingo and Antonia's case reveal that when imperial ongoing mobility forced personal matters into the public sphere, individuals' true desires often contradicted their initial testimonies and their prescribed societal obligations.